1977
DOI: 10.1007/bf00562897
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma concentrations and pharmacological effects of labetalol

Abstract: In healthy normal subjects following the administration of labetalol the pharmacological effects were measured and compared with the plasma concentrations achieved. The inhibition of exercise induced tachycardia and inhibition of exercise induced increases in systolic pressure were significantly related to the administered dose of labetalol. Labetalol was rapidly absorbed from the gastrointestinal tract and peak plasma concentrations occurred two hours after oral administration. There was a linear correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2

Year Published

1979
1979
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 15 publications
1
22
2
Order By: Relevance
“…It has been previously shown, (Richards, Maconochie, Bland, Hopkins, Woodings & Martin, 1977) that labetalol is rapidly absorbed after oral administration, peak plasma concentrations occurring within 2 h. In addition, the same workers showed that there was a rapid decline in plasma concentrations although inhibition of exercise-induced tachycardia persisted longer than 4 h. Our observations would suggest that by 6 h after a single oral dose of 100 mg, blood pressure is returning towards pre-treatnent levels. After single doses of 400 mg, the duration of the hypotensive response was greater than after 100 mg.…”
Section: Discussionsupporting
confidence: 67%
“…It has been previously shown, (Richards, Maconochie, Bland, Hopkins, Woodings & Martin, 1977) that labetalol is rapidly absorbed after oral administration, peak plasma concentrations occurring within 2 h. In addition, the same workers showed that there was a rapid decline in plasma concentrations although inhibition of exercise-induced tachycardia persisted longer than 4 h. Our observations would suggest that by 6 h after a single oral dose of 100 mg, blood pressure is returning towards pre-treatnent levels. After single doses of 400 mg, the duration of the hypotensive response was greater than after 100 mg.…”
Section: Discussionsupporting
confidence: 67%
“…There are no published data on the relative antihypertensive effects of the various isomers. Limited acute pharmacokinetic studies have been reported (Martin et al, 1976;Richards et al, 1977;Louis et al, 1978), suggesting variable bioavailability. The present report is a detailed study of the pharmacokinetics of labetalol following acute single dose administration of 100 and 200 mg.…”
Section: Introductionmentioning
confidence: 99%
“…Since the calculated plasma labetalol concentration midway between trough and peak levels (midpoint concentration) correlated significantly with plasma labetalol Css (Figure 5) this may provide a reliable estimate of the latter. Plasma labetalol Css correlated with the daily dose despite the extensive first-pass elimination which has been described following oral administration (Richards et al, 1977).…”
Section: Discussionmentioning
confidence: 83%
“…Considerable variation in plasma labetalol concentrations is likely to occur between individuals after oral administration because of extensive firstpass metabolism of the drug (Richards, Maconochie, Bland, Hopkins, Woodings & Martin, 1977) and to investigate this further, the pharmacokinetics and effects of labetolol were studied both between and within individual hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%